Radio frequency/analog and linearity performance of a junctionless double gate metal–oxide–semiconductor field-effect transistor. (November 2017) - Baral, Biswajit; Biswal, Sudhansu Mohan; De, Debashis; Sarkar, Angsuman
The analog/radio frequency (RF) and linearity performance of a junctionless double gate metal–oxide–semiconductor field-effect transistor (JL DGMOS) is investigated using the numerical TCAD device simulator. JL DGMOSs have shown great promise for high-performance digital applications due to their superior short channel effect performance and ease of fabrication. In analog and RF circuit applications, linearity testing and RF performance is a major issue that is encountered due to non-linear behavior of the devices. Therefore, in this paper, different RF/analog and linearity performance figures of merits such as transconductance, intrinsic gain, the transconductance generation factor, the cut off frequency, the maximum frequency of oscillation, the gain bandwidth product, the variable intercept point of second order, the variable intercept point of third order, inter modulation distortion, the third-order intercept point, and 1-dB compression have been presented. Moreover, the effect of gate-length downscaling on these performance parameters has been carried out. The results indicate that the down scaled JL DGMOS shows great promise to become a competitive contender for analog/mixed signal system on chip applications by demonstrating a significant improvement in its RF performance with gate-length downscaling.